EFFECTS OF HERDERS- FARMERS CONFLICTON GIRL CHILD EDUCATION IN NUAMAN LOCAL GOVERNMENT AREA, ADAMAWA STATE - NDOYA TSUNDUDAYA ISHAKU; MOMSIRI B. MAIGARI; UMAR ILIYA; HELEN PATRICK (International Studies Journal)
This study examined the effects of Herders farmers clashes on Girl Child Education in Numan local government area. the study reveals that as a result of the clashed, many girls’ child in numan local government are badly affected because they are being subjected to kidnaping, rape and abduction. The research also reveals that most of the reasons behind the clashes were as a result of scarce space for agricultural and grazing activities in the area and the menace has eating deeply into the fabrics of the local government. The research also highlighted the recent efforts made by Government and Non-governmental organizations in the areas affectted by Herder’s farmers clashes to improve access to Girl Child Education. some of the research objectives are: to ascertain the effects of clash on girl child education, to uncover some of the efforts made by various policy makers in tackling insecurity. It was recommended among others that religious/ traditional leaders and Community-Based Organizations should actively encourage girls' Education in their respective communities and government should be proactive in combatting insecurity in the area affected in other to improve girl child education. The methodology used in gathering information is qualitative research design such ascontent analysis from text books, journal, internet material. Conflict theory was also used a guiding frame work of the research.